What drives inflation perceptions? : a dynamic panel data analysis - Dohring, Bjorn; Mordonu, Aurora; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2007)
At the moment of the euro cash changeover, inflation perceptions in the euro area deviated from measured inflation, and in some euro-area Member States in a persistent way. In recent years, a growing body of literature has developed on the factors that might explain this deviation. This paper formally tests various explanations advanced in this literature. It adopts a cross-country perspective at the level of the euro area which is empirically implemented through a dynamic panel data model. Inflation perceptions are found to be highly persistent (the autoregressive term is large and statistically highly significant). In contrast to much of the - descriptive - literature, an index of "out-of-the-pocket expenditure" is found not to explain inflation perceptions better than does the all-items HICP index. As suggested by psychological experiments, inflation expectations seem to contribute to the formation of inflation perceptions, although to a limited extent. Prices of residential real estate contribute significantly to inflation perceptions, suggesting that households have a broader view of the cost of living when forming inflation perceptions. Our results have implications for policy, for the further research agenda and for the development of statistics. In particular, the persistence of inflation perceptions makes us think that communication efforts prior to euro introduction are essential to anchor perceptions. Once perceptions increase, it will be much harder to bring them back in line with measured inflation.
Economic Papers